The Effect of Skill Exercises to Build Kinetic Programs Using Teaching Methods According to VARK Model in Learning Peaceful Correction (Journal of the College of Basic Education, 2020)
The study aimed to prepare skill exercises accompanied by special educational methods according to the vark model to learn some of the offensive skills in basketball. The effect of the skill exercises associated with the special educational means according to the vark model in building the animation programs of some offensive basketball skills :Experimental and control. The study sample included the students of the first grade in the Department of Physical Education and Sports Sciences / Faculty of Isra University for the academic year (2018-2019) and the number of (420) students and for morning study only. The researcher then prepared training exercises accompanied by special educational methods according to the VARK model. The educational program included (11) educational units with one learning unit per week for the duration of the educational unit (90) minutes. The researcher concluded that the exercises prepared by him are effective in learning some of the basketball offensive skills of the experimental group according to the FARC model and in different percentages and that the Mahjen adopted by the teachers of the material is effective in learning the offensive skills of basketball for the control group according to the model FARC and different rates and diversity in the use of skill exercises Which is associated with teaching methods has an effective and positive effect in learning some offensive skills in basketball. The researcher also recommends the use of skilled exercises in learning some of the offensive basketball skills in the faculties of physical education and sports sciences because of their positive impact And effective in the learning process. It is also recommended to use special teaching aids to assist with each pattern of learning.